2014
DOI: 10.1080/02772248.2014.987511
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to titanium dioxide (TiO2) induces oxidative stress in zebrafish gill tissues

Abstract: Titanium dioxide (TiO 2 ) produced globally is estimated to reach 6.8 million tonnes in 2016. Extensive use of TiO 2 will thus result in environmental exposure to these nanoparticles (NP). At present there is limited information on the ecotoxicolgical consequences of TiO 2 NP exposure focusing on aquatic life. Hence, the aim of this study was to examine toxicity of TiO 2 NP to address the risks using a zebrafish model system. In both qualitative and quantitative analysis, TiO 2 NP was found to accumulate in gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Additionally, the downregulation of bax and bid gene expressions indicated that the NPA could inhibit the death of fish. The result suggested that the NPA was favorable for the growth of fish. …”
Section: Results and Discussionmentioning
confidence: 97%
“…Additionally, the downregulation of bax and bid gene expressions indicated that the NPA could inhibit the death of fish. The result suggested that the NPA was favorable for the growth of fish. …”
Section: Results and Discussionmentioning
confidence: 97%
“…The accumulations of CuO‐NPs were in conformity with the incorporation of silver (Ag) NPs in zebrafish embryos (Park et al ., ). Similarly, nanotitania bioaccumulation was also reported in the adult zebrafish (Purushothaman et al ., ). In a study on HepG2 cells, CuO‐NPs dissolution into Cu ions was established in both the intracellular level and culture media (Cuillel et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In zebrafish, the increase in ROS after chronic exposure to TiO2-NPs is observed along with changes in antioxidant enzymes, such as glutathione S-transferase (GST), catalase (CAT) and superoxide dismutase (SOD) (BAR-ILAN et al, 2012;TANG;ZHANG;ZHU, 2019). The redox imbalance can result in oxidation of cellular components, which affects cell integrity and alters mechanisms such as signaling, proliferation and cell death (PURUSHOTHAMAN et al, 2014;WANI;SHADAB, 2020). In nanoparticle-induced inflammation, neutrophils and macrophages produce ROS via an inflammation-signaling pathway, resulting in lipid peroxidation and consequently tissue damage (BRAND et al, 2020).…”
Section: Discussionmentioning
confidence: 99%